Monitoring the Risk Factors Associated with Asthma among Saudi Adults in Najran - N. K. Elfaki; A. Y. Shiby (Challenges in Disease and Health Research Vol. 5, 2021)
Background: Asthma is a chronic illness that affects people of all ages. Its prevalence has risen over the last few decades in Saudi Arabia. The aim of this study was to explore the common risk factors that associated with asthma among Saudi adults in Najran during the period December 2016 to October 2017. One hundred eighty four patients who were over 18 years of age and who had a diagnosis of definite asthma (cases), beside another 184 healthy individuals as control group, that matched the cases in terms of age and sex constituted the study sample. A questionnaire as a tool of data collection was completed by cases as well as from controls. It was consisting of data that include personal, familial and indoor environmental factors that could be potential risk factors for asthma. The mean ages for cases and controls were 21.3 (± 16.5) and 21.7 (± 16.8) years respectively. Each group consisted of 108 (58.7%) males beside 76 (43.3%) females. There were no significant association between asthma occurrence and level of education and indoor plants with P-value >0.05. On the other hand, multivariate logistic regression analysis showed that family history (OR=5.01 and CI=2.09-8.42), using sprays of insecticides or air fresheners (OR=8.5, CI=2.34-11.09), as well as rhinitis (OR=4.76, CI=2.19-6.45) were significantly associated with asthma occurrence. Additionally, active or passive smoking was significantly (P-value= 0.041 and 0.012) associated with asthma among adults in Najran. Based on the obtained results, it was concluded that there are different risk factors patterns for asthma, those factors appear to play a major role and likely contribute to the magnitude of this burden. It was concluded that family history, smoking, allergic rhinitis and smoking the most risk factors for developing asthma among Saudi adults. Further studies for investigating other factors were recommended. Moreover, health education programs for educating people about the risk factors, preventive measures, early diagnosis and proper management were highly recommended.